Angażowanie pracowników w doskonalenie systemu zarządzania - Urbaniak, Maciej (The employees commitment to the improvement of management system, 2008)
Improving management systems with the use of the PDCA cycle, enterprises are not only interested in the implementation of quality management system (conform to ISO series 9000), environmental management system (conform to ISO 14001 / EMAS), occupational health and safety management system (conform to OHSAS / PN - N 18001), but more and more they are using the others operational management tools like Toyota Production System (kaizen, 5S/TPM), Lean Management or Six Sigma methodologies (DMAIC, DMADV/DFSS). More and more they are integrating these tools to achieve the effect of synergy in continuous improvement of the organizations. The integration of these tools has the positive impact on raising people’s awareness and their commitment to achieve organizational excellence.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 434-452